Physical And Mental Health Examination Of Lung Tb Patients Due To The Covid-19 Pandemic And Health Education In Increasing Patient Knowledge - Pariyana; Dewi Angrraini; Hanna Marsinta Uli; Dalilah; Muhammad Aziz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Pulmonary tuberculosis is an infectious disease that is still a major global health problem. Pulmonary TB cases are one of the co-morbidities of death for COVID-19 patients. The increase in the prevalence of TB patients and the increase in the number of cases and deaths of COVID-19 will certainly have an impact on patients and their families. The spread of COVID-19 worries the public, causing feelings of pressure and anxiety which are a common response from people who are affected (either directly or indirectly). The purpose of this activity is to describe the health status of pulmonary TB patients, both physical health and mental health in the working area of ​​the Merdeka Palembang Health Center. The participants of this activity were 28 patients who were present at the Merdeka Palembang Health Center in November 2021. The results of this activity showed that the patient characteristics were mostly adults (20-60 years) as many as 21 people (75%), most of them were male 19 people (67.9%), 10 people with high school education (35.7%), work as laborers as many as 6 people (21.4%), body mass index mostly normal and underweight that is 10 people each (35.7%), most of them have poor knowledge 21 people (75%) and most of them do not experience anxiety as many as 22 people (78.6%), patients who experience mild anxiety 4 people (14.3%) moderate and severe anxiety each 1 person (3.6%). The results of the measurement of health status based on lipid profile examination showed that pulmonary TB patients had a mean cholesterol level of 141.53±31.42, an average triglyceride of 90.82±20.15, a mean HDL of 32.42±3.20, and an average LDL of 92.03. ±22.07.